2019
DOI: 10.1021/acs.jproteome.9b00009
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of Tissues with Laser Ablation for Proteomics: Comparison of Picosecond Infrared Laser and Microsecond Infrared Laser

Abstract: It was recently shown that sampling of tissues with a picosecond infrared laser (PIRL) for analysis with bottom-up proteomics is advantageous compared to mechanical homogenization. Because the cold ablation of tissues with PIRL irradiation is soft, proteins remain intact and even enzymatic activities are detectable in PIRL homogenates. In contrast, it was observed that irradiation of tissues with a microsecond infrared laser (MIRL) heats the tissue, thereby causing significant damage. In this study, we investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Compared to our previous studies [ 4 , 15 , 16 ] the total number of identified proteins are in the same order of magnitude, but with a significantly smaller ablation volume in this study. With regards to the study of Kwiatkowski et al (2016) [ 4 ] the ablation volume was reduced 100-fold down to 0.5 µL.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations
“…Compared to our previous studies [ 4 , 15 , 16 ] the total number of identified proteins are in the same order of magnitude, but with a significantly smaller ablation volume in this study. With regards to the study of Kwiatkowski et al (2016) [ 4 ] the ablation volume was reduced 100-fold down to 0.5 µL.…”
Section: Discussionsupporting
confidence: 39%
“…Compared to mechanical homogenization, this is a very gentle method of sample extraction and homogenization, avoiding time-consuming preparation steps. Over the past decade, this tissue sampling and homogenization has been successfully demonstrated with a PIRL, nanosecond infrared laser (NIRL) and even a high-energy microsecond infrared laser (MIRL) with subsequent mass spectrometric proteomics [ 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] or directly coupled to real-time MS instruments, such as the “SpiderMass” technology [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be assumed that their importance will increase in the coming years. Laser systems working with different wavelengths can be used to ablate large biomolecules, such as DNA or proteins, as well as smaller metabolites and elements [32,33]. Some analytical platforms also enable the direct nontargeted measurement of food samples without any extraction, for example by means of infrared (IR) spectroscopy [34] (near IR [NIR] [35], mid IR [36]), Raman spectroscopy [37]) as well as different ionization sources for MS: direct analysis in real time (DART) [38], desorption electrospray ionization (DESI), rapid evaporative ionization mass spectrometry (REIMS) [39], liquid extraction surface analysis (LESA) [40], or laser ablation electrospray ionization (LAESI).…”
Section: Sample Extractionmentioning
confidence: 99%